Molecular epidemiology and virulence factors in Streptococcus agalactiae - Florindo, Carlos Alberto Lopes (2016)
Fundação para a Ciência e a Tecnologia (FCT) - PhD Project (SFRH/BD/48231/2008: PTDC/SAU-MII/105114/2008 and DAAD scholarship/2010)